Understanding the Multifaceted Challenges of Immigrant Women Workers in Nepal - Gurung, Namrata Grace; Mainali, Sunita (NPRC Journal of Multidisciplinary Research, 2026)
Background: Labour migration is a cornerstone of Nepal's economy, yet policy and research have predominantly focused on the outbound migration of Nepali citizens. This focus has rendered a significant population nearly invisible: immigrant women workers who migrate to Nepal from other countries, primarily India and Bangladesh. Concentrated in informal, unregulated sectors like domestic work, caregiving, and hospitality within urban centers, these women face unique and severe vulnerabilities. While global scholarship highlights the precarious position of migrant women, and Nepal has recently adopted progressive human rights frameworks like the National Action Plan on Business and Human Rights (2024–2028), the specific realities of immigrant women workers within Nepal remain critically under-examined.Objective: This study aims to analyze the multifaceted challenges faced by immigrant women workers in Nepal. It seeks to understand how intersecting structures of gender, class, nationality, and legal status shape their labour conditions and lived experiences. Furthermore, it critically examines the effectiveness of Nepal's migration governance and human rights frameworks in addressing the protection, rights, and access to justice for this marginalized workforce.Methods: The study employs a qualitative methodology, combining critical policy analysis with an integrative literature review. It draws on three main sources: (1) academic literature from feminist sociology and intersectionality scholarship; (2) grey literature and policy documents, including national labour laws, migration policies, and the National Action Plan on Business and Human Rights; and (3) secondary data from national statistics and migration databases. This data is analyzed through a gender-responsive and intersectional lens to identify gaps between policy commitments and the lived realities of immigrant women workers.Findings: The analysis reveals that immigrant women workers in Nepal experience profound marginalization due to the convergence of multiple factors. Their employment in the informal economy places them outside the purview of standard labour protections, leading to wage exploitation, unsafe working conditions, and harassment. This vulnerability is compounded by their immigration status, which may be irregular or undocumented, creating barriers to reporting abuse and accessing justice. Nepal's migration governance frameworks are found to be structurally biased towards outbound migration, with existing policies and human rights commitments failing to extend meaningful protection to inbound workers. This policy gap, combined with social isolation, language barriers, and gendered assumptions about their work, leaves immigrant women in a legally precarious and highly exploitable position.Conclusion: The study concludes that the vulnerabilities of immigrant women workers in Nepal are not incidental but are systematically produced and reinforced by intersecting structural inequalities and significant gaps in the national governance framework. The protections promised by policies like the National Action Plan on Business and Human Rights remain largely inaccessible to this group. Bridging this protection gap requires a paradigm shift towards a gender-responsive and intersectional approach that extends labour rights, monitoring, and grievance mechanisms to all workers within Nepal's borders, regardless of their origin or documentation status.Novelty: This research addresses a critical lacuna in migration studies by shifting the analytical lens from Nepal as a source country to Nepal as a destination country for women labour migrants. It is among the first studies to systematically apply an intersectional framework to the specific context of immigrant women workers in Nepal, foregrounding their invisibility within both policy and scholarship. By connecting their lived experiences to a critical analysis of national and international human rights frameworks, the study provides a foundational evidence base for developing more inclusive and rights-based migration governance.